Caregivers' Barriers to Disclosing the HIV Diagnosis to Infected Children on Antiretroviral Therapy in a Resource-Limited District in South Africa: A Grounded Theory Study - Sphiwe Madiba; Kebogile Mokwena (AIDS Research and Treatment)
We used a grounded theory approach to explore how a sample of caregivers of children on antiretroviral treatment (ART) experience HIV disclosure to their infected children. This paper explores caregivers' barriers to disclosing HIV to infected children. Caregivers of children aged 6–13 years who were receiving ART participated in four focus-group interviews. Three main themes, caregiver readiness to tell, right time to tell, and the context of disclosure, emerged. Disclosure was delayed because caregivers had to first deal with personal fears which influenced their readiness to disclose; disclosure was also delayed because caregivers did not know how to tell. Caregivers lacked disclosure skills because they had not been trained on how to tell their children about their diagnosis, on how to talk to their children about HIV, and on how to deal with a child who reacts negatively to the disclosure. Caregivers feared that the child might tell others about the diagnosis and would be discriminated and socially rejected and that children would live in fear of death and dying. Health care providers have a critical role to play in HIV disclosure to infected children, considering the caregivers' expressed desire to be trained and prepared for the disclosure.